2021
DOI: 10.1186/s43591-021-00004-0
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic fibers affect dynamics and intensity of CO2 and N2O fluxes from soil differently

Abstract: Microplastics may affect soil ecosystem functioning in critical ways, with previously documented effects including changes in soil structure and water dynamics; this suggests that microbial populations and the processes they mediate could also be affected. Given the importance for global carbon and nitrogen cycle and greenhouse warming potential, we here experimentally examined potential effects of plastic microfiber additions on CO2 and N2O greenhouse gas fluxes. We carried out a fully factorial laboratory ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 73 publications
(101 reference statements)
5
12
0
Order By: Relevance
“…MPs also reduce N 2 O emissions during extensive nitrogen fertilization. The effects of MPs on GHGs emissions should be considered in future impact evaluations, and the soil structure should be examined to better understand such impacts [159,160]. Furthermore, chemically changing processes will not eliminate the enormous amount of emissions produced, despite the possibility that the development of renewable energy-based polymeric materials could reduce GHG emissions from production units [138].…”
Section: Impact Of Micro and Nano Plastics On Ecosystem Services And Climate Changementioning
confidence: 99%
“…MPs also reduce N 2 O emissions during extensive nitrogen fertilization. The effects of MPs on GHGs emissions should be considered in future impact evaluations, and the soil structure should be examined to better understand such impacts [159,160]. Furthermore, chemically changing processes will not eliminate the enormous amount of emissions produced, despite the possibility that the development of renewable energy-based polymeric materials could reduce GHG emissions from production units [138].…”
Section: Impact Of Micro and Nano Plastics On Ecosystem Services And Climate Changementioning
confidence: 99%
“…Several studies have shown that MNPs influence greenhouse gas emissions [ 94 , 159 , 160 ]. There is a need to properly understand the processes responsible for this phenomenon.…”
Section: Uptake Of Soil Micro and Nanoplastics In Plantsmentioning
confidence: 99%
“…Microplastics could therefore favour the substrate suitable for the proliferation of these bacteria with increased production of N 2 O and CO 2 caused by their nitrifying and carbon crystallizing activity, respectively. The consequences would also lead to changes in the pH of the water as well as the release of greenhouse gases (Rillig et al, 2021).…”
Section: Effect On Algaementioning
confidence: 99%